2021
DOI: 10.3390/ijms22126629
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal System Biology and Smoke Damage: From Basic Science to Medical Clinic

Abstract: Cigarette smoking has a negative impact on the skeletal system, as it reduces bone mass and increases fracture risk through its direct or indirect effects on bone remodeling. Recent evidence demonstrates that smoking causes an imbalance in bone turnover, making bone vulnerable to osteoporosis and fragility fractures. Moreover, cigarette smoking is known to have deleterious effects on fracture healing, as a positive correlation between the daily number of cigarettes smoked and years of exposure has been shown, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The density of the bone is a commonly used indicator for indexing patients' bone quality 35 and it changes significantly during disease and/or as a function of various physiological and lifestyle variations. [37][38][39] In this study, the bone density of the mandible was approximately 1.76 ± 0.38 g/cc, which was about 5% below the value reported in literature 40 and therefore, considered as "normal" and used for calculating other "bone conditions." Thus, the bone density was varied ±20% to simulate different bone conditions.…”
Section: Assignment Of Materials Properties and Defining "Bone Condit...mentioning
confidence: 55%
See 1 more Smart Citation
“…The density of the bone is a commonly used indicator for indexing patients' bone quality 35 and it changes significantly during disease and/or as a function of various physiological and lifestyle variations. [37][38][39] In this study, the bone density of the mandible was approximately 1.76 ± 0.38 g/cc, which was about 5% below the value reported in literature 40 and therefore, considered as "normal" and used for calculating other "bone conditions." Thus, the bone density was varied ±20% to simulate different bone conditions.…”
Section: Assignment Of Materials Properties and Defining "Bone Condit...mentioning
confidence: 55%
“… ρgoodbreak=1.028goodbreak+()0.000769goodbreak×HU Egoodbreak=2349goodbreak×ρ2.15 As a result, since each individual element had a distinct ρ and E , the meshed mandible would have an inhomogeneous distribution of material properties, which was useful for better simulating the inherent patient‐specific nature of bone's material. The density of the bone is a commonly used indicator for indexing patients' bone quality 35 and it changes significantly during disease and/or as a function of various physiological and lifestyle variations 37–39 . In this study, the bone density of the mandible was approximately 1.76 ± 0.38 g/cc, which was about 5% below the value reported in literature 40 and therefore, considered as “normal” and used for calculating other “bone conditions.” Thus, the bone density was varied ±20% to simulate different bone conditions.…”
Section: Methodsmentioning
confidence: 73%
“…This also explains the early onset of menopause in female smokers, with the consequent effects of this condition on bone health [ 218 ]. However, it is unclear which of the toxins found in cigarettes are specifically related to the alteration of bone health [ 219 ].…”
Section: Treatment Of Osteoporosis and Novel Approachesmentioning
confidence: 99%
“…Smoking also induces inflammatory processes and increases oxidative stress, generating damage to the collagen metabolism, which acts as an important biochemical marker in bone metabolism in addition to inducing toxicity on bone cells by increasing the resistance to calcitonin, which blocks bone angiogenesis [ 223 ], preventing the creation of new blood vessels, which would alter the flow of oxygen and nutrients to the bone [ 224 ]. In addition to the inverse association between smoking and body weight described in the evidence, it has been shown that cigarette consumption is associated with low weight due to the inhibitory effect of nicotine on appetite [ 219 ].…”
Section: Treatment Of Osteoporosis and Novel Approachesmentioning
confidence: 99%
“…MBDs are usually caused by an individual’s internal malformations in skeletal cellular components or by anomalies in calcium and phosphorus homoeostatic processes ( Bonakdarpour, 2009 ), with osteoporosis being the most common. A generalized decrease in bone mass results from an imbalance between the rates of osteogenesis and osteoclast, which can have numerous causes, the most significant of which is estrogen insufficiency in post-menopausal women ( Tarantino et al , 2021 ). Osteomalacia is a mineralization deficiency caused by the lack of calcium or phosphorus, or by deficient osteoblast activity ( Anderson et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%